Mapping Land Subsidence in Ahmedabad City, India: Interpreting InSAR-Derived Land Subsidence with Auxiliary Data - A. Pandit; N. Ahuja; S. Sawant; J. Mohite; S. Pappula (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
In this study, we mapped land subsidence in the Ahmedabad urban region using the SBAS InSAR technique between 2020 and 2023 (approximately 3.5 years). A distinct pattern of average line of sight (LOS) land subsidence was observed at two key locations within the city: the Southwest and Southeast regions of Ahmedabad. The average LOS velocity in these areas ranged from −1.5 cm/year to −3.0 cm/year in the Southwest and −2 cm/year to −3.5 cm/year in the Southeast. Negative LOS velocities represent areas experiencing subsidence. Data from the Central Ground Water Board (CGWB) revealed that groundwater levels in the Southwest region dropped significantly from around 11 meters in mid-2005 to less than 2 meters by 2019. Similarly, in the Southeast, groundwater levels fell from approximately 42 meters in 2005 to around 28 meters in 2019. The observed land subsidence was strongly correlated with localized groundwater depletion. Additionally, groundwater data from multiple wells across the Ahmedabad district were analyzed over several years. In contrast to localized depletion, a substantial number of wells at the district level showed an increase in groundwater levels from 2014 to 2022, compared to the decadal average, suggesting an overall positive trend in groundwater availability. This indicates that the subsidence is likely due to localized over-extraction of groundwater and hydrogeological factors specific to these areas, which differ from broader regional trends.